Barriers to participation in BRAC RDP - Evans, Timothy G.; Mohammed, Rafi; Adams, Alayne M.; Chowdhury, Mushtaque (BRAC Research and Evaluation Division (RED), 2019)
As part of the BRAC RDP Impact Assessment Study (lAS), a participatory wealth ranking exercise stratified households into four socio-economic groups: groups 1 and 2 being wellendowed with land, assets and generally without survival worries; group 3 households having marginal land holdings, minimal assets and resources devoted exclusively to survival; and finally a "4th group" in which household viability is threatened by poverty, ill-health and other adversities. Although both 3rd and 4th group households are eligible to participate in BRAC RDP, concern about the accessibility of the Programme to the destitute "4th group" along with a general ignorance about the characteristics of this group, provided the rationale for this study. Its purposes are: 1. to establish the prevalence of household poverty in rural Bangladesh and the rate of BRAC RDP participation; 2. to elicit the circumstances which inhibit the "4th group" from participating in BRAC RDP; and 3. to identify changes in the structure of RDP, or the need for new initiatives, to improve their well-being. In August through to October 1994, a field survey was undertaken in five well-established, good functioning RDP Area Offices (AOs). Ten percent of the Village Organizations (VOs) in each of these AOs were selected for the sample (78 VOs in 55 villages). Key informants enumerated all households in the sample villages, and, employing Rapid Rural Appraisal (RRA), ranked them into 3 wealth groups: 1. wealthy households; 2. poor households: and 3. very poor households ( 11,805). In each village, 30 households were selected for interview--! 0 RDP members. I 0 eligible non-members, 5 former members, and 5 ineligible or non-target group (NTG) households. Structured questionnaires containing sections on household composition, health, past crises. socio- economic status and BRAC membership were administered to 1637 households.